Effect of water temperature on the selectivity of monofilament gill nets (PA) - Duman, Erdal; Pala, Murat (Asian Network for Scientific Information, 2007)
In this study, the selectivity feature of monofilament gill nets used in the Keban Dam Lake, varying with water temperature changing with the seasons was investigated in this research. The research was conducted between 20.07.2001 and 02.07.2002 (13 months) on the Keban Dam Lake (Elazig/Turkey). Two, monofilament (PA) gill nets with 100 m length and 100 mesh height with two different mesh widths (50 and 60 mm) were used in the research. During this research with the gill nets, two fish species (Capoeta trutta and Barbus rajanorum mystaceus) were most often caught and these with high economic value were taken into account. Important changes depending on the temperature were determined particularly on monofilament gill nets made out of thin material (0.23 mm) and having a mesh width of 50 mm. The Capoeta trutta species showed significant differences with monofilament gill nets with both 50 and 60 mm mesh width in relation to the water temperature. © 2007 Asian Network for Scientific Information.
Keywords: Gill net; Polyamide; Selectivity; Temperature